Keabsahan Perjanjian Financial Technology Peer To Perr Lending (P2P Lending) Di Indonesia - Nur Hidayatul Fithri; Budi Endarto; Muhamad Chaidar (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The existence of fintech P2P Lending can help Indonesian people who are still unreached by banking services to borrow funds with easy, fast terms and without making a direct agreement. Electronic lending system make it easy public to borrow funds with easy reuqirements and without need to meet for make a agreement. Trading system transaction originally paper based and then shift to electronic based system (digital) is something that needs to be studied further about validity of the e-contract as the basis of relations between two parties that make agreement, by using legal protection theory, legal certainty theory, and theory of justice. The purpose of this research is to study together validity of e-contract in Fintech P2P Lending industry. The results of this research analysis show that the practice of online lending and borrowing based on fintech P2P Lending still does not have legal certainty for loan recipients, the benchmark for the validity of an agreement in fintech P2P Lending only refers to article 1320 of the Civil Code regarding the conditions for the validity of the agreement. The Fintech Lending Law should be drafted immediately to guarantee legal certainty for P2P Lending fintech.